Consequences of Adolescent Pregnancy on Maternal and Neonatal Health: A Narrative Review - Lawot, Isabel; Bajracharya, Karuna; Acharya, Sabitri (Journal of Nursing Education of Nepal, 2023)
Introduction: Adolescent pregnancy, classified as pregnancies occurring between the ages of 13 to 19, is a multifaceted and crucial public health concern that affects both the young mother and her newborn. The physiological and psychosocial immaturity of the adolescent mother presents distinctive challenges during pregnancy. Moreover, the effects of teenage pregnancy extend beyond the prenatal phase, influencing neonatal well-being and the long-term health paths of both the mother and child. The purpose is to review the literature and evaluate the impacts of adolescent pregnancy on both mothers and neonates. Methods: A review of literature and journal publications was conducted by searching through various databases, including PubMed, CINHL, Science Direct, Cochrane, and Google Scholar. A specific search approach was applied for each database. Initially, 627 titles were retrieved, and after screening, 10 articles were chosen for a more detailed evaluation. Ultimately, 10 articles met the specific criteria for inclusion in the study. Results: The findings indicated that adolescent pregnancy is linked to a higher likelihood of maternal health complications like anemia, pre-eclampsia, eclampsia, post-partum hemorrhage, and adverse neonatal outcomes, including preterm birth, low birth weight, and prolonged Neonatal Intensive Care Unit (NICU) admission. Conclusion: Adolescent pregnancy leads to higher rates of maternal and neonatal complications. Therefore, it is crucial to provide health education, and support programs for teenage mothers. DOI: https://doi.org/10.62143/8t9pav21